2022
DOI: 10.1021/acs.biochem.2c00104
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Acetylation of α-Synuclein Slows down Its Aggregation Process and Alters the Morphology of the Resulting Aggregates

Abstract: Parkinson’s disease is associated with the aberrant aggregation of α-synuclein. Although the causes of this process are still unclear, post-translational modifications of α-synuclein are likely to play a modulatory role. Since α-synuclein is constitutively N-terminally acetylated, we investigated how this post-translational modification alters the aggregation behavior of this protein. By applying a three-pronged aggregation kinetics approach, we observed that N-terminal acetylation results in a reduced rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 75 publications
(165 reference statements)
1
17
1
Order By: Relevance
“…Fibrils formed from acetylated α-synuclein have a different morphology compared to the unmodified protein. Thus, a reduced amount of β-structure was found in their structure [ 75 ].…”
Section: Protein Folding and Aggregationmentioning
confidence: 99%
“…Fibrils formed from acetylated α-synuclein have a different morphology compared to the unmodified protein. Thus, a reduced amount of β-structure was found in their structure [ 75 ].…”
Section: Protein Folding and Aggregationmentioning
confidence: 99%
“…Although the protofibrils formed by N‐terminal acetylated proteins were morphologically similar to those formed by non‐acetylated α‐synuclein, their growth rate was slower. Moreover, Michele Vendruscolo's group [74] further investigated the effect of N‐terminal acetylation modification on the aggregation behavior of α‐synuclein using the thioflavin labeling method. The results are shown in Figure 5, where N‐terminal acetylation led to a decrease in the rate of lipid‐induced aggregation and slowed down the pro‐fibril‐catalyzed proliferation of aggregation at the same concentrations.…”
Section: N‐terminal Acetylationmentioning
confidence: 99%
“…Various PTMs regulate α-synuclein susceptibility to aggregation by changing its conformation. PTMs such as phosphorylation, ubiquitination, acetylation, nitration, SUMOylation, etc., modify α-synuclein physicochemical properties and affect the aggregation process in synucleinopathies [ 11 , 12 , 29 , 31 , 32 , 33 , 34 ]. α-Synuclein is acetylated constitutively at its N-terminal ( Figure 1 ).…”
Section: α-Synuclein Misfolding Aggregation and Fibrillationmentioning
confidence: 99%
“…α-Synuclein is acetylated constitutively at its N-terminal ( Figure 1 ). As Bell et al recently demonstrated [ 11 , 12 ] this PTM changes the charge and spatial structure of α-synuclein and affects its aggregation and interaction with lipid membranes. Even subtle disturbances caused by PTMs as well as mutations, can lead to remarkable alterations in the aggregation performance of this protein [ 11 , 12 ].…”
Section: α-Synuclein Misfolding Aggregation and Fibrillationmentioning
confidence: 99%
See 1 more Smart Citation